Achados oculares ultrassonográficos em toxoplasmose congênita com ênfase no estudo da microftalmia - Manoella Almeida Ilgenfritz de Moraes (2019)
Introduction: Toxoplasmosis is the major etiology of infectious posterior uveitis worldwide, being particularly severe in immunosuppressed individuals and in children with congenital infection. Ocular ultrasound can be useful to characterize eye changes associated with congenital toxoplasmosis, including microphthalmia. Microphthalmia is often poorly/subjectively defined by external examination, with no previous reports of systematic application of ocular ultrasound in congenital toxoplasmosis. Objective: To characterize ocular ultrasound findings in patients with congenital toxoplasmosis in the first year of life and a decade later. To determine the prevalence of microphthalmia in congenital toxoplasmosis measuring the axial eye length using ultrasound. To evaluate eye growth by measuring the axial eye length. Methods: Retrospective analysis of prospective investigation on neonatal screening for congenital toxoplasmosis in the state of Minas Gerais. Newborns screened with anti-Toxoplasma gondii IgM from November 2006 to May 2007 and confirmed with congenital toxoplasmosis were included. Microphthalmia was defined according to nomogram from Weiss et al. (1989) in the first year of life, and according to Sampaolesi (1984) and Bardajkian et al. (2004) for the eleventh to the twelfth years of life. In addition to complete ophthalmic examination, including indirect ophthalmoscopy, Us was performed in children in the first year of life (median 72 days) using UltraScan (Alcon Laboratories, Forth Worth, TX, EUA) with 10-MHz B-scan, measuring the axial length of the eye. The Us was repeated 10 years later, also with A-scan (biometry). Visual acuity was measured in the children with five to six years of age. Statistical analysis included Fisher exact, Wilcoxon, Chi-square, t student and McNemar tests, with a p-value of <0.05. Results: Ultrasound exam was performed in 96 patients in the first year of life, 82 with congenital toxoplasmosis and 14 subsequently considered uninfected. For evaluation of the first Us exam, patients were divided in three groups: congenital toxoplasmosis with retinochoroiditis, congenital toxoplasmosis without retinochoroiditis and patients without congenital toxoplasmosis. The following ultrasound changes were found, with these respective frequencies among the three groups: vitreous echoes (42.3%; 7.2%; 14.3%); macular irregularity (29.3%; 4.9%, 0%); posterior vitreous detachment (12.2%, 7.3%; 0%); and choroidal thickening (12.2%, 2.4%; 3.6%). Only the group with congenital toxoplasmosis and retinochoroiditis had microphthalmia (21.1%), vitreous membranes (18.7%), retinal detachment (8.9%) and intraocular calcification (2.4%). Microphthalmia was detected by Us in 26 eyes (15.9% of eyes with TC) of 14 patients (17.1% of patients with TC), being bilateral in 12 (85.7%), and in equal numbers for both sexes. In the first fundoscopy of the microphthalmic eyes, ten (38.5%) had retinal detachment. In the eyes with microphthalmia, the macula exam was possible in 19 - 17 eyes (89.5%) with macular retinochoroiditis and two (10.5%) with peripheral retinochoroiditis. Microphthalmia was associated with neurologic involvement (71.4% x 11.8%; P<0.05), strabismus (76.9% x 32.8%; P<0.05), nystagmus (61.5% x 6.0%; P<0.05) and visual acuity < 20/1000 (38.9% x 2.6%; P<0.05). Ten years later, Us in 33 patients with TC and retinochoroiditis revealed, respectively vitreous echoes (33.3%; 72.7%); macular irregularity (22.7%; 34.8%); microphthalmia (10.6%; 13.6%); and vitreous membranes (24.2%; 21.2%); calcification (3.0%; 10.6%); DR (7.6%; 6.1%); posterior flattening of ocular wall (24.2%); and phthisis bulbi (3.0%), both only ten years later. Conclusions: Us is a simple and reliable method to assess ocular changes in congenital toxoplasmosis, and also useful to determine microphthalmia in an objective way. Microphthalmia in children with toxoplasmosis was associated with RD in the first year of life, and also with strabismus, nystagmus, visual disability and significant CNS involvement. This may suggest more diffuse systemic involvement in these cases, likely relate to earlier infection during intrauterine life. Microphthalmia may be an easily identifiable Us marker of more severe ocular and neurologic involvement in congenital toxoplasmosis.